Analisis Strategi Promosi Melalui Sosial Media Instagram Pada Daya Tarik Wisata Pantai Gunung Payung - Marindra, Adya Putri; Moniaga, Natasha Erinda Putri (JURNAL DESTINASI PARIWISATA; Vol 12 No 1 (2024): VOL 12, NO 1 (2024): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2024)
The research titled "Analysis of Promotion Strategies through Instagram Social Media for the Tourist Attraction of Gunung Payung Beach" is a qualitative descriptive study aimed at determining how digital promotion strategies on the Instagram social media platform are employed by the management to promote Gunung Payung Beach as a tourist attraction in Bali. By conducting interviews with the manager of Gunung Payung Beach and observing various social media platforms used, it is evident that the strategies employed by Gunung Payung Beach on their Instagram account are quite effective, based on the Kotler and Armstrong promotional mix concept, which includes five aspects: Advertising, Personal Selling, Direct Marketing, Sales Promotion, and Public Relations. Keywords: Marketing Strategy, Marketing Mix, Social Media, Instagram, Tourist Attraction.